2018
DOI: 10.1016/bs.mie.2017.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Allostery with Avatars to Design Inhibitors Assessed by Cell Activity: Dissecting MRE11 Endo- and Exonuclease Activities

Abstract: For inhibitor design, as in most research, the best system is question dependent. We suggest structurally defined allostery to design specific inhibitors that target regions beyond active sites. We choose systems allowing efficient quality structures with conformational changes as optimal for structure-based design to optimize inhibitors. We maintain that evolutionarily related targets logically provide molecular avatars, where this Sanskrit term for descent includes ideas of functional relationships and of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 111 publications
(150 reference statements)
0
23
0
Order By: Relevance
“…Next, we determined whether MRN favors the transcriptional activity of RNAPII beyond promoting its recruitment to DSBs. Previous cellular experiments showed that mirin, a molecule that restricts the access of MRE11 to dsDNA and inhibits its nuclease activity ( Moiani et al., 2018 ; Shibata et al., 2014 ), inhibited the transcription of dilncRNA ( Michelini et al., 2017 ), suggesting that the nuclease activity of MRE11 may be involved. We hypothesized that the ability of MRNs to resect DSBs to generate 3′ protruding DNA ends could provide an ideal DNA substrate for transcription by RNAPII ( Kadesch and Chamberlin, 1982 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we determined whether MRN favors the transcriptional activity of RNAPII beyond promoting its recruitment to DSBs. Previous cellular experiments showed that mirin, a molecule that restricts the access of MRE11 to dsDNA and inhibits its nuclease activity ( Moiani et al., 2018 ; Shibata et al., 2014 ), inhibited the transcription of dilncRNA ( Michelini et al., 2017 ), suggesting that the nuclease activity of MRE11 may be involved. We hypothesized that the ability of MRNs to resect DSBs to generate 3′ protruding DNA ends could provide an ideal DNA substrate for transcription by RNAPII ( Kadesch and Chamberlin, 1982 ).…”
Section: Resultsmentioning
confidence: 99%
“…To strengthen our conclusion that MRN stimulates RNAPII activity by melting DNA using an independent approach, we used small-molecule allosteric inhibitors of MRN activities ( Shibata et al., 2014 ). While PFM39 inhibits exonuclease activity, PFM01 attenuates the endonuclease activity of MRN ( Moiani et al., 2018 ; Shibata et al., 2014 ), and mirin was shown to reduce both activities ( Deshpande et al., 2016 ). We next performed our transcription assays with MRN and RNAPII in the presence of mirin, PFM39, or PFM01 ( Shibata et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, structural information on MR has emerged from prokaryotes that can provide more accessible structures than have been analyzed for their eukaryotic counterparts. In fact, prokaryotic Mre11 is used as a molecular avatar (an embodiment of human MRE11–essential features) for design of inhibitors against human MRE11 (47). Excitingly, high-resolution structures of eukaryotic MRN protein domains are also being solved (33, 38, 39).…”
Section: Mrn Complex: Structural Biochemistry and Biologymentioning
confidence: 99%
“…Moreover, ensemble readout from SAXS is well suited to detecting selective stabilization of transient conformations by ligand interactions. Development of allosteric modulators of protein ensembles has come increasingly into focus for drug targeting, as these ligands avoid competitive interplay with endogenous ligands [ 132 134 ]. The move to target small-molecules toward protein complexes and assemblies to more effectively modulate signaling pathways is well aligned to these advantages of SAXS-based approaches for screening and structure-function analysis.…”
Section: Ht Screening With Saxs: Current and Emerging Applicationsmentioning
confidence: 99%